Preparation and Characterization of Multi-Component Catalysts for the Oxidative Coupling of Methane - Huang, Kai; Ni, Songbo; Lu, Keqiang (Asian Journal of Chemistry, 2011)
A multi-component catalyst Na-Mn-Zr-W-S-P/SiO2 is prepared and tested in a fixed-bed microreactor without inert gases as thinners. The average methane conversion and the C2 hydrocarbon selectivity in the oxidative coupling of methane are about 35 and 70 %, respectively. The yield of C2 hydrocarbon is more than 25 %. The catalysts are characterized by X-ray diffraction, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. Mn2O3 is suggested to be the main active species in the catalysts, while the addition of Zr further activates the methane molecules. The addition of W and P efficiently improves C2 selectivity and inhibits deep-oxidation of SiO2. Sodium easily combines with WO4.